Images of Antique Cities and “Fire Landscapes” in West European Art of the 16th century - Kostyria, Maksim A. (Actual Problems of Theory and History of Art, 2015)
The article aims to trace the emergence and development of the so-called “Fire Landscapes” in West European art of the 16th century, as well as to consider the iconography of the depicted ancient cities. Landscapes with fires were common in art of the epoch. They derive from the works of H. Bosch who was the first to use an image of burning city for representation of the Hell. In Italy this image was linked to a specific historical or mythological event. Most often painters depicted either burning Rome or Troy. Three reasons underlay popularity of the genre. Foremost, it was significantly influenced by the historical situation: looting of large cities occurred during numerous wars in Italy and Northern Europe. Secondly, classic literature was an inexhaustible source of this kind of plots. Colourful descriptions of disasters in the works of antique historians and poets formed the basis for paintings and graphic works of the Renaissance masters. Finally, the notions of “variety” and “terribilita” associated with Leonardo and Michelangelo could be embodied anew within the framework of the topic. This, of course, was a distant echo of these concepts, because they had evolved to external decoration and theatrical effects.
Keywords: Antique cities; Fire Landscape; Italy; The Netherlands; 16th century; painting; engraving; theory; Leonardo; Michelangelo